Retifanlimab Vs Avelumab in Patients with Metastatic Merkel Cell Carcinoma: A Cost Utility Analysis in Italy - Ghetti, Gianni; Porta, Camilla; Povero, Massimiliano (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
OBJECTIVE: Merkel cell carcinoma (MCC) is a very rare and aggressive neuroendocrine skin cancer, characterized by a 5-year survival rate of 13.5% in patients with distant metastases. This study aimed to evaluate the cost-utility of retifanlimab compared to avelumab in the treatment of metastatic MCC patients who had not received prior systemic therapies, from the perspective of the Italian National Health Service (SSN).METHODS: A 7-day cycles partitioned survival model with three mutually exclusive health-states—progression-free, post-progression and death—was developed to compare lifetime clinical outcomes and costs for patients treated with retifanlimab versus avelumab in the Italian context. Progression-free survival and overall survival curves were modelled independently, with POD1UM-201 trial data used for retifanlimab efficacy. In the absence of direct head-to-head clinical trial data, avelumab efficacy was estimated using the hazard ratio obtained from a matching-adjusted indirect comparison. Following a previous National Institute for Health and Care Excellence submission, utility values were derived using a timeto-death approach, with health states defined as “>266 days to death”, “35-266 days to death”, and “